2011
DOI: 10.1007/s12119-011-9111-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Deaf Individuals’ Dating Scripts Follow the Traditional Sexual Script?

Abstract: The current study investigated Deaf individuals' dating expectations. Prior research on dating expectations has identified three common scenes: initiation/ meeting, activities, and outcomes/conclusions. Participants were asked to report their expectations for each scene on a typical date. Talking was the most frequently occurring initiation activity. Dinner and a movie were among the top date activities in the activities scene. Activities were often reported as group gatherings. Dating outcomes included a good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
3
0
4
Order By: Relevance
“…Our results indicated that these participants did not conform to the TSS (Byers, 1996), which was also found in previous research studying the TSS with Deaf women (Gilbert et al, 2012). These differences appear to be cultural and this study begins to expand some of these differences in sexual desire, sexual satisfaction, and even sexual expectations.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our results indicated that these participants did not conform to the TSS (Byers, 1996), which was also found in previous research studying the TSS with Deaf women (Gilbert et al, 2012). These differences appear to be cultural and this study begins to expand some of these differences in sexual desire, sexual satisfaction, and even sexual expectations.…”
Section: Discussionsupporting
confidence: 83%
“…These behaviors are part of the Traditional Sexual Script (TSS) that is culturally transmitted (Clark, Carroll, Bartoli, & Taylor, 2009). In a parallel study, Deaf college students shared their dating expectations, which differed from those found in Bartoli and Clark. Deaf and hard of hearing participants' expectations did not include the TSS; rather they focused more on group dating, did not mention sexual limiting by the woman, and infrequently discussed intercourse as part of a typical date (Gilbert, Clark, & Anderson, 2012). These results are in contrast to the hearing college students' responses where all of the older students' expectations for a typical date focused on a one-on-one event between a man and a woman.…”
Section: Sexual Development In Deaf and Hearing Womenmentioning
confidence: 73%
See 2 more Smart Citations
“…No Quadro 1 são apresentados os autores, título, ano de publicação, instituição e objetivos de cada estudo analisado. Portanto, foi possível identificar que, quanto aos temas estudados, seis pesquisas abordaram a sexualidade através das experiências sexuais, dos mitos e relacionamentos (Gilbert, Clark, & Anderson, 2012;Gomez, 2011;Joharchi & Clark, 2014;Jhai, 2017;Lehane, Dammeyer, Hovaldt, & Elsass, 2017;Wienholz, Seidel, Michel, Haeussler-Sczepan, & Riedel-Heller, 2016); cinco versaram sobre violência e/ou abuso sexual (Anderson & Leigh, 2011;Anderson & Pezzarossi, 2012Porter & Williams, 2011;Powers et al, 2009); três destacaram a saúde sexual (Aldana, 2012;Pacher, Costa, Nascimento, Moura, & Passos, 2015;Umoren & Adejumo, 2014); e uma se referiu à homossexualidade (Abreu, Silva, & Zuchiwschi, 2015 ...continuação…”
Section: Figuraunclassified